2012
DOI: 10.4103/0976-9668.101894
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Tinea capitis in school going children in Kolkata, West Bengal

Abstract: Background:In recent years the incidence of Tinea capitis, infection of scalp by dermatophytes, has increased in United Kingdom and North America. The trend may be similar in India. The objective of this study is to find the prevalence of Tinea capitis in school going urban children in Kolkata, West Bengal state.Materials and Methods:The present study is a cross-sectional study conducted in a government higher primary school in Kolkata.Results:Totally 505 students were screened and 52 were diagnosed to have Ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 6 publications
2
22
2
Order By: Relevance
“…These findings are consistent with those of some previous studies but differ from others that found infestations to be the most common skin disorders . In addition, tinea capitis accounted for the majority of fungal infections, as observed in previous studies carried out in pediatric populations . Its prevalence in our population was 24.6%, which is similar to those in other population‐based studies carried out in schoolchildren in low‐income countries, especially in Ethiopia, except for a study carried out by Ali et al .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings are consistent with those of some previous studies but differ from others that found infestations to be the most common skin disorders . In addition, tinea capitis accounted for the majority of fungal infections, as observed in previous studies carried out in pediatric populations . Its prevalence in our population was 24.6%, which is similar to those in other population‐based studies carried out in schoolchildren in low‐income countries, especially in Ethiopia, except for a study carried out by Ali et al .…”
Section: Discussionsupporting
confidence: 92%
“…found different distributions of fungal isolation amongst the three communities, which is highly suggestive of a child‐to‐child transmission pattern. Further, asymptomatic carriers may be an important source of anthroponotic transmission . Figueroa et al .…”
Section: Discussionmentioning
confidence: 99%
“…Male gender, having family member with a dermatophyte infection, not using tap water, and sharing combs significantly predicted tinea capitis. Similar observations have been reported from previous studies 9,15,18,21,22 investigating primary school children.…”
Section: Dermatophyte Infectionssupporting
confidence: 92%
“…The superficial layers of the epidermis, particularly the stratum corneum, and the keratin rich appendages, such as the hair and nails of the living host, are invaded by these dermatophytes, where they eventually proliferate and multiply. [1] It is a common scalp infection seen in children from developing countries, often causing varying degrees of hair loss. [23]…”
Section: Introductionmentioning
confidence: 99%